Validity and Reliability of Turkish Version of Short Questionnaire to Assess Healthcare Professionals’ Perceptions of Asynchronous Telemedicine Services - Karadag, Mehmet; Huzmeli, Irem; Dogru Huzmeli, Esra (Progress in Nutrition, 2022)
Study Objectives: The purpose of this study was to translate the "Short Questionnaire to Assess Healthcare Professionals’ Perceptions of Asynchronous Telemedicine Services" into Turkish, and analyze it for validity and reliability. Methods: A total of 80 individuals were accepted in this cross-sectional descriptive study. The original scale was translated into Turkish (forward translate, reconciliation, back translation, review, plot test, final scale). Cronbach alpha, exploratory and confirmatory factor analysis were employed to assess the reliability and validity of the measurement model. Results: Cronbach’s alpha was obtained as 0.880 in the Quality and 0.829 in the Difficulties subscales. The overall alpha value was 0.885. ICC (95% CI) values of the scale were calculated as 0.841 (0.775 to 0.891). RMSEA=0.09 was observed below the acceptable level of 0.10; GFI=0.92, AGFI=0.81 above the acceptable threshold of 0.90. Conclusion: The Turkish version of the scale is valid and reliable, and can be used in studies evaluating healthcare professionals’ perceptions of asynchronous telemedicine services.